2019
DOI: 10.3390/medicina55080487
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Children’s Birth Weight and Birth Length and a Risk of Overweight and Obesity in 4–15-Year-Old Children

Abstract: Background and Objectives. The purpose of the study was to investigate the relationship between children’s birth weight/length and a risk of overweight and obesity. Materials and Methods. The study involved 747 children from kindergartens, as well as primary and middle schools from southeastern Poland. All the subjects were examined on fasting status. Each child was examined for body mass and height, in order to calculate their body mass index (BMI), and BMI centile. The parents completed a questionnaire relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…The U-shaped relationship between the birth length and risk of hospitalization early in life due to all causes was found among Japanese children [44]. And the relationship between a lower birth length and risk of overweight and obesity in boys was found in the study which involved 747 children in southeastern Poland [45]. Prenatal MA exposure affecting the birth length of infants was found by Abar et al [18], Eze et al [24], Lagasse et al [41], Diaz et al [21], Shah et al [26], and the data in some studies also show a decreasing tendency but there was no statistical difference [19,22,25].…”
Section: Birth Lengthmentioning
confidence: 86%
“…The U-shaped relationship between the birth length and risk of hospitalization early in life due to all causes was found among Japanese children [44]. And the relationship between a lower birth length and risk of overweight and obesity in boys was found in the study which involved 747 children in southeastern Poland [45]. Prenatal MA exposure affecting the birth length of infants was found by Abar et al [18], Eze et al [24], Lagasse et al [41], Diaz et al [21], Shah et al [26], and the data in some studies also show a decreasing tendency but there was no statistical difference [19,22,25].…”
Section: Birth Lengthmentioning
confidence: 86%
“…Several studies have shown inconsistent results, suggesting that further research on this topic is necessary. 9 , 23 , 24 , 25 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…В работе Joanna Baran и соавт. отмечалась связь массы тела при рождении с ИМТ, но не было обнаружено значительных различий в массе тела при рождении между детьми с избыточной массой тела или ожирением и детьми с нормальной массой тела [27]. Дети, которые были рождены недоношенными, также имели более высокие шансы развития ожирения по сравнению с доношенными новорожденными [28].…”
Section: период новорожденности и раннего возрастаunclassified
“…Не вызывает сомнений связь вида вскармливания и ИМТ ребенка. Вероятность развития ожирения выше у детей на искусственном вскармливании или получавших грудное молоко в течение короткого времени [29] по сравнению с детьми, которых кормили грудью не менее 6 мес [27]. Напротив, грудное вскармливание более 6 мес было связано со снижением риска избыточной массы тела у детей в возрасте 2 лет [30].…”
Section: период новорожденности и раннего возрастаunclassified